Analysis of Data Structure and Algorithm Visualization (International Journal of Food and Nutritional Sciences, 2022)
An essential component of algorithm design is visualization. The analysis of data structures and algorithms has traditionally been theoretical and mathematical form. This makes it time-consuming, challenging to study, and lacking in comprehension of how a problem is implemented in real life. This restricts the size and scope of conceptual ideas. It has always been more and more important to see the data structure and algorithm. Due to the prominence of web development, we must make sure that we create applications that visualize algorithms and data structures along with how they are implemented in practice. There have been progressed and offered the concept, data structures, and methods that can achieve the target and goal to aid pupils and their practical use helps both students and teachers visualize data structures and algorithms. Given the increasing desire and necessity for sharing and exploring knowledge, information retrieval is a field of study that is gaining popularity. For a very long time, the focus of computer science research has been on data structures. The requirement for effective data structures has increased vital given the exponential growth of the data. Data structures are required to organize information more practically for sophisticated applications. There are many different information structures, but we must select the one that best fits the layout. A review of several information structure types has been conducted to identify their properties divisions, etc. The processing and organization of the data and files already in the system require a certain degree of sophistication. By adopting the non-synchronized methodology of storage and management, no brute force approaches can minimize and manifest it so quickly, but it may be positioned such that it doesn't get in the way and is also simple to grasp.